2017
DOI: 10.1039/c6ta10521a
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced doping on reduced PEDOT

Abstract: Doping of the reduced (undoped) PEDOT by oxygen during oxygen reduction reaction (ORR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(141 citation statements)
references
References 31 publications
(38 reference statements)
4
135
0
2
Order By: Relevance
“…This is however unlikely since PEDOT:PSS already is in a doped state and further doping is difficult to achieve since a higher concentration of polarons will lead to overoxidation that degrades the polymer. [30] As is evident from the FTIR-spectra, there are no significant peak shifts and therefore the change in conductivity must be due to a morphological change (i.e., secondary doping). However, to be sure that the doping state is unchanged, we performed FTIR-ATR measurements on PEDOT:PSS with and without ARS.…”
Section: Secondary Dopant Effect By Arsmentioning
confidence: 95%
“…This is however unlikely since PEDOT:PSS already is in a doped state and further doping is difficult to achieve since a higher concentration of polarons will lead to overoxidation that degrades the polymer. [30] As is evident from the FTIR-spectra, there are no significant peak shifts and therefore the change in conductivity must be due to a morphological change (i.e., secondary doping). However, to be sure that the doping state is unchanged, we performed FTIR-ATR measurements on PEDOT:PSS with and without ARS.…”
Section: Secondary Dopant Effect By Arsmentioning
confidence: 95%
“…Later, they synthesized the PEDOT microflowers and found these PEDOT microflowers suppress the unwanted side reaction. Mitraka et al . revealed that the PEDOT electrode is electrochemically reduced (undoped) in the voltage range of ORR regime, which means it has a low conductivity.…”
Section: Carbon‐free Materialsmentioning
confidence: 99%
“…The EDS analysis clearly shows that the polymer is present throughout the fiber wall (location 1042 to 1047 in Figure 2c and location 139 to 141 in Figure 2f), in both types of samples, indicating sufficient penetration of the EDOT monomer through the fiber wall during impregnation. [31] At moderate negative potentials, versus the Ag/AgCl reference potential, the presence of oxygen and ORR in itself renders PEDOT relatively more conducting as compared to applying the same negative potentials to PEDOT while maintained in a N 2 atmosphere. This also indicates that the monomer penetrates the fiber wall from two directions: from the fiber surroundings and from the inner core (lumen) of the fiber.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…Moreover, in both i-OS and i-CS CF-PEDOT samples, the polymer content is relatively higher on the surface (location 1042, 1044, 1045, and 1047 in Figure 2c and location 139 and 141 in Figure 2f) of the fiber wall as compared to the middle of the wall. [31] The increase in conductivity, upon exposure to O 2 , is essential when using the conducting polymer as the air electrode in fuel cell applications. However, the absolute amount of polymer in the two types of CF-PEDOT samples (i-OS vs i-CS systems) differs vastly; in fact, the CF walls of the i-OS CF-PEDOT samples contain up to five times more PEDOT while comparing with the i-CS samples, thus indicating the difficulty of the EDOT monomer to penetrate the collapsed fiber walls.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
See 1 more Smart Citation